An Android Augmented Reality Application to Improve Cognitive Skills in Color Recognition for Down Syndrome children - Gunawan, Tania Irena; Istiono, Wirawan (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The objective of this research is (1) to develop and construct an educational Augmented Reality game that focuses on colour recognition for individuals with down syndrome, using markerless based method. (2) Measure the level of user acceptance towards color recognition educational games with AR technology and the markerless method. (3) Measuring the increase in knowledge of Down Syn-drome children in recognizing colors to hone the cognitive skills of early child-hood. Down Syndrome is a common genetic disorder in humans. Children with Down syndrome have three copies of chromosome 21. This condition affects the physical, cognitive, and social development of these children. In this research, a color recognition educational game was created by adding Augmented Reality (AR) technology which aims to attract children with Down syndrome. This re-search was successfully implemented and approved by 84.8% of parents of Down Syndrome children. The results showed a significant increase in the post-quiz compared to the pre-quiz, indicating an increase in children's grades